2015
DOI: 10.4155/bio.15.82
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Sensitive and Fast UHPLC–MS/MS Method for Determination of Clopidogrel, Clopidogrel Acid and Clopidogrel Active Metabolite H4 in Human Plasma

Abstract: With LLOQ of 0.05 ng/ml for clopidogrel and H4, and 5.5 min LC gradient, it is the most sensitive and fastest method to our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The derivatization process with MPB does not differentiate between the racemic H4 (active) and H3 (inactive) stereoisomer of clopidogrel metabolites, potentially leading to some measurement error. While high concordance between H3 and H4 has been noted previously [21], which may minimize the import of this potential limitation, the use of novel methodologies to isolate the H4 isomer, such as the method developed by Hua and colleagues [22], may improve variant detection in future studies. Additionally, all work presented herein was conducted in the Amish of Lancaster, PA, which could influence translatability of findings to non-Amish populations.…”
Section: Discussionmentioning
confidence: 91%
“…The derivatization process with MPB does not differentiate between the racemic H4 (active) and H3 (inactive) stereoisomer of clopidogrel metabolites, potentially leading to some measurement error. While high concordance between H3 and H4 has been noted previously [21], which may minimize the import of this potential limitation, the use of novel methodologies to isolate the H4 isomer, such as the method developed by Hua and colleagues [22], may improve variant detection in future studies. Additionally, all work presented herein was conducted in the Amish of Lancaster, PA, which could influence translatability of findings to non-Amish populations.…”
Section: Discussionmentioning
confidence: 91%
“…The PK profiles of vicagrel, clopidogrel, their common metabolites 2-oxo-clopidogrel and AM-H4 were characterized via a bottom-up approach integrating available physicochemical and in vitro absorption, distribution, metabolism and excretion information. The models were successfully verified and validated for clopidogrel and AM-H4 but not vicagrel and 2-oxoclopidogrel because of the difficulty of determination in plasma and limited clinical data (Hua et al, 2015;Liu et al, 2019). The irreversible inhibition of platelet aggregation of thienopyridines was characterized by an indirect response model and linked to plasma concentrations of AM-H4.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CLOP, an ofcial monograph was published for it in the USP and revealed that CLOP could be analyzed using a special column for HPLC analysis, and the absorbance is measured at 220 nm [16]. In addition, many studies have aimed to develop diferent methods of analysis of CLOP individually [17,18] or in combination using diferent technologies such as HPLC [19][20][21], ultra-high performance liquid chromatography (UHPLC) [22], UV spectrophotometric method [23], and thin layer chromatography (TLC) [24]. When performing our research, none of these studies had developed an analytical method for simultaneously determining APX and CLOP in the same dosage form using any spectrophotometric method.…”
Section: Introductionmentioning
confidence: 99%